Khubilai Khan's Lost Fleet : History's Greatest Naval Disaster - Delgado, James (London The Bodley Head, 2009)
The true story of history's greatest naval disaster -the destruction of Khubilai Khan's immense armada.
Include Maps, Illustrations, Sources, Notes, Index.
History's Greatest Naval Disaster.
Keywords: Mongols -- Japan -- Attempted Mongol Invasions of Japan (1274-1281) -- Military leadership